Marcin Poczobut-Odlanicki, Józef Epifani Minasowicz and Franciszek - Lis-Listwon, Agnieszka (Senoji Lietuvos literatūra, 2021)
The research concerns the publishing activity of three editors of the Age of Enlightenment: Marcin Poczobut-Odlanicki, Józef Epifani Minasowicz, and Franciszek Bohomolec. All three of them were very diligent, thorough, philologicly-aware, and attentive not only to the language of their works, but also to their moral tenor. Despite differences in background, education and main profession (PoczobutOdlanicki was a renowned astronomer and a rector of the Principal School of Lithuania (later, Vilnius Academy); Minasowicz was mainly a writer and an editor (of Monitor, among other titles), and Bohomolec was a pedagogue and also a writer), all three possessed a common trait which, according to the author, contributed to their publishing diligence: they were educated in Jesuit colleges where much emphasis was put on the humanities, and students were taught both in Latin and in Polish. The research is based on selected publications they had edited: Pamiątka stoletnia zwycięstwa pod Wiedniem przez Jana III Króla polskiego nad Turkami otrzymanego roku 1683/ z woli prześwietnej Komissyi Edukacyi Narodowej przez Szkołę Główną w X. Lit. Uroczyście ochodzonej dnia 11. I 12. Października roku 1783 (A commemorative centenary of the victory at Vienna by Jan III, King of Poland, over the Turks achieved in 1683/ solemnly celebrated by the Principal School of the Grand Duchy of Lithuania on 11 and 12 October 1783 by the will of the illustrious Commission of National Education ) edited by Poczobut-Odlanicki, Zbiór mniejszy poezji polskich drobniejszych (A Small Collection of Minor Polish Poetry) edited by J.E. Minasowicz, and Zabawki oratorskie (Oratorical Games) edited by Franciszek Bohomolec. The author chose these books as representative of the publishing activity of the above-mentioned editors and because of their diverse nature: they contain many different texts, also by other authors, editorial comments, and are coloured by the linguistic correctness characteristic of the three editors. An analysis of these sources made it possible to distinguish common characteristics of these publications and to make the assumption that it was the education at Jesuit colleges that had shaped the publishing thoroughness and diligence shared by all three editors.